Pharmacokinetic and Pharmacodynamic Integration and Modeling of Enrofloxacin in Swine for Escherichia coli - Wang, Jianyi; Hao, Haihong; Huang, Lingli; Liu, Zhenli; Chen, Dongmei; Yuan, Zonghui (Frontiers in Microbiology, 2016)
The aim of this study was tooptimize the dose regimens of enrofloxacin to reduce the development of fluoroquinolone resistance in Escherichia coli (E.coli) using pharmacokinetic/pharmacodynamic (PK/PD) modeling approach. The single dose (2.5 mg/kg body weight) of enrofloxacin was administered intramuscularly (IM) to the healthy pigs. Using cannulation, the pharmacokinetic properties, including peak concentration (Cmax), time to reach Cmax (Tmax) and area under the curve (AUC), were determined in plasma and ileum content. The Cmax, Tmax, and AUC in the plasma were 1.09 ± 0.11 μg/mL, 1.27 ± 0.35 h and 12.70 ± 2.72 µg•h/mL, respectively. While in ileum content, the Cmax, Tmax and AUC were 7.07 ± 0.26 μg/mL, 5.54 ± 0.42 h and 136.18 ± 12.50 µg•h/mL, respectively. Based on the minimum inhibitory concentration (MIC) data of 918 E.coli isolates, an E.coli O101/K99 strain (enrofloxacin MIC = 0.25 μg/mL) was selected for pharmacodynamic studies. The in vitro minimum bactericidal concentration (MBC), mutant prevention concentration (MPC) and ex vivo time-killing curves for enrofloxacin in ileum content were established against the selected E.coli O101/K99 strain. Integrating the in vivo pharmacokinetic data and ex vivo pharmacodynamic data, a sigmoid Emax (Hill) equation was established to provide values for ileum content of AUC24h/MIC producing, bactericidal activity (52.65 h) and virtual eradication of bacteria (78.06 h). A dosage regimen of 1.96 mg/kg every 12 h for 3 days should be sufficient in the treatment of E.coli.